Inhibition of mycelial growth of fungi associated with anthracnose in yam (Dioscorea alata) - Arce-Araya, Cinthia; Varela-Benavides, Ingrid; Torres-Portuguez, Sergio (Agronomía Mesoamericana, 2019)
Introduction. Yam is a tuber affected by a large number of organisms such as viruses, bacteria and fungi, being Colletotrichum, which causes anthracnose, the most important. Objective. The objective of the present research was to determine, through an in vitro test, the inhibition exerted by commercial fungicides on the mycelial growth of seven fungal isolations that had been obtained from foliar lesions in yam. Materials and methods. The study was carried out at the Instituto Tecnológico de Costa Rica, in the period between October 2016 and June 2017. Ten fungicides —azoxystrobin, benomyl, benzotiazol, carbendazine, chlorothalonil, mancozeb, mancozeb + copper oxychloride, methylthiophanate, propiconazole, and propineb— were evaluated at different concentrations, on five isolates of Colletotrichum, one of Bipolaris and one of Mycoleptodiscus. With this purpose, two tests were performed; in the first, the growth of the isolates in PDA was analyzed in five different concentrations of each fungicide. The results obtained were subsequently used in the second test to calculate the percentage of inhibition of mycelial growth (PICM) of each isolation. Results. The results indicate that, in the concentrations used and with the fungal isolates studied, no treatment reached 100 % inhibition. Propineb was the most effective fungicide on the fungus Mycoleptodiscus sp., with a PICM of 64.51, carbendazim had a similar behavior on Colletotrichum truncatum with a PICM of 43.83, and propiconazole had it on Colletotrichum gloeosporioides with a PICM of 49.79. Azoxystrobin was not effective at any concentration on any isolation. Conclusion. The results obtained suggest that the pathogens associated with anthracnose in Costa Rican yam plantations could be developing resistance to fungicides.